GEREJA KATOLIK DALAM BAYANG-BAYANG KONFLIK PAPUA – JAKARTA - Meki Mulait (Studia Philosophica et Theologica, 2017)
The Catholic Church is not the only church and religion that carries out God’s mission of integral human salvation in Papua. He is one of several churches and other religions that carry out the mission. Despite many shortcomings, the Church continues to be faithful in carrying out its mission. The conflict between the Indonesian government and the Papuan people who want the right of self-determination to take place since the 1960s until now has become a challenge for the Church to continue its mission consistently. Consistent Church attitudes must be seen in a position of defense against justice, truth and human safety. The from beginning when Papua began to flare up, the Catholic Church played a central axis role. This means that the Church does not support the “M” aspiration for the Papuan people and the way the Indonesian government defends Papua by force. The Catholic Church as a unifier with other churches and religions chooses the path of dialogue with the parties concerned to keep promoting and fighting for a peaceful Papua apartfrom carrying out the proclaiming of faith and human development in all aspects of life. Gereja Katolik bukan hanya gereja dan agama yang menyampaikan misi Allah tentang penyelamatan manusia integral di Papua. Ia adalah salah satu dari bagian gereja-gereja dan agama-agama lain yang membawa misi. Meskipun banyak kekurangan, Gereja melanjutkan dengan setia misinya. Konflik di antara pemerintah Indonesia dan orang Papua yang menginginkan hak dari tujuan diri sudah terjadi sejak tahun 1960-an sampai sekarang menjadi sebuah tantangan untuk Gereja dalam melanjutkan misinya secara konsisten. Sikap-sikap Gereja yang konsisten harus dilihat dalam sebuah posisi pertahanan menghadapi keadilan, kebenaran dan keselamatan manusia. Dari awal ketika Papua mulai bergelora, Gereja Katolik memainkan peranan sentral. Ini berarti bahwa Gereja tidak mendukung aspirasi “M” untuk orang Papua dan cara pemerintah Indonesia mempertahankan Papua dengan kekuatan. Gereja Katolik sebaga sebuah pemersatu dengan gereja-gereja dan agama-agama yang lain memilih jalur dialog dengan partai-partai yang berfokus untuk meningkatkan dan berperang untuk sebuah Papua yang damai terpisah dari penyelesaian tentang iman dan perkembangan manusia dalam semua aspek kehidupan